Brain-derived neurotrophic factor levels and anemia in elementary school children - Ena Juhaina; Rostika Flora; Rico Januar Sitorus; Mohammad Zulkarnain; Ahmad Fickry Faisya; Nur Alam Fajar; N Nurlaili (Universitas Aisyah Pringsewu, 2020)
Iron deficiency can cause BDNF deficits in some areas of the brain. BDNF has an essential role in brain function especially memory and learning and is reported to be low in Iron Deficiency Anemia (ADB) in animal studies. ADB is vulnerable in the age group of children. The purpose of this study was to analyze the relationship between levels of Brain-Derived Neurotrophic Factor (BDNF) with the incidence of anemia in elementary school children in Seluma District. This research is an analytical observational study with a cross-sectional study design conducted in April 2019 of 50 respondents of elementary school children aged 9-12 years in Seluma Regency. Venous blood sampling was performed to measure serum BDNF levels using the Enzyme-Linked Immunosorbent Assay (ELISA) method. Hb levels are measured using the Easy Touch tool. Statistical analysis using the Chi-square test. Based on the measurement results of serum BDNF levels obtained 46% of children have BDNF levels below the average (less than 3258,6084 ng/mL). Based on the results of Hb measurements, there is 30 percent of children with anemia. Bivariate analysis showed no significant relationship between BDNF levels with anemia, the Prevalence Odds Ratio (POR) was 2,250. The staff of community health center can collaborate with schools to provide counseling about anemia and its effects on school children.Kadar brain-derived neurotrophic factor dan anemia pada anak sekolah dasarAbstrakDefisiensi zat besi dapat menyebabkan defisit BDNF di daerah tertentu dari otak. BDNF memiliki peran penting dalam fungsi otak khususnya memori dan pembelajaran dan dilaporkan rendah pada Anemia Defisiensi Zat Besi (ADB) dalam penelitian pada hewan. ADB rentan terjadi pada kelompok umur anak-anak. Tujuan penelitian ini adalah untuk menganalisis hubungan antara kadar Brain Derived Neurotrophic Factor (BDNF) dengan kejadian anemia pada anak Sekolah Dasar di Kabupaten Seluma. Penelitian ini merupakan penelitian obsevasional analitik dengan rancangan studi cross-sectional dilaksanakan pada bulan April 2019 terhadap 50 responden anak Sekolah Dasar yang berusia 9-12 tahun di Kabupaten Seluma. Dilakukan pengambilan darah vena untuk mengukur kadar BDNF serum dengan menggunakan metode Enzyme-Linked Immunosorbent Assay (ELISA). Kadar Hb diukur dengan menggunakan alat Easy Touch. Analisis statistik menggunakan uji Chi square. Berdasarkan hasil pengukuran kadar BDNF serum diperoleh 46% anak mempunyai kadar BDNF di bawah rata-rata (kurang dari 3258,6084 ng/mL). Berdasarkan hasil pengukuran Hb terdapat 30% anak anemia. Analisis bivariat menunjukkan tidak ada hubungan yang bermakna antara kadar BDNF dengan anemia, Prevalence Odds Ratio (POR) adalah 2,250. Petugas Puskesmas dapat melakukan kolaborasi dengan pihak sekolah untuk memberikan penyuluhan tentang anemia dan dampaknya bagi anak sekolah.